2016
DOI: 10.1007/s12539-016-0182-7
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderic Acid A Targeting β-Catenin in Wnt Signaling Pathway: In Silico and In Vitro Study

Abstract: Wnt signaling pathways are the group of signaling transduction controlling the embryonic development, cell proliferation, cell migration, cell fate specification, and body axis pattern. Nuclear accumulation of β-catenin in Wnt signaling is a widely recognized marker of poor cancer prognosis which regulates fat and glucose metabolism. Ganoderic acid is a triterpene isolated from fungus Ganoderma lucidum renowned for its pharmacological effects. The present study revealed the mechanistic study of β-catenin with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Although lactate dehydrogenase can be inhibited by galloflavin without affecting the energetic balance of normal tissues, 37 ROS production, and expression of lactose‐synthesizing genes are not altered. As described in previous studies, ganoderic acid is a substrate with antioxidant activities, intracellular ROS scavenging, inhibition of the glucose metabolic shift (including glucose uptake, lactate production, pyruvate, and acetyl‐coenzyme production), insulin sensitivity accelerating, and amelioration of glucose homeostasis and inhibition of NF‐κB 33‐36 . In our study, treatment of cells with ganoderic acid A under the high dose of glucose reduced fermentative glycolysis and ROS production but greater lactose concentration and expression of lactose synthesis genes, indicating its role in benefiting for lactation of MECs under the high glucose dose.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although lactate dehydrogenase can be inhibited by galloflavin without affecting the energetic balance of normal tissues, 37 ROS production, and expression of lactose‐synthesizing genes are not altered. As described in previous studies, ganoderic acid is a substrate with antioxidant activities, intracellular ROS scavenging, inhibition of the glucose metabolic shift (including glucose uptake, lactate production, pyruvate, and acetyl‐coenzyme production), insulin sensitivity accelerating, and amelioration of glucose homeostasis and inhibition of NF‐κB 33‐36 . In our study, treatment of cells with ganoderic acid A under the high dose of glucose reduced fermentative glycolysis and ROS production but greater lactose concentration and expression of lactose synthesis genes, indicating its role in benefiting for lactation of MECs under the high glucose dose.…”
Section: Discussionsupporting
confidence: 80%
“…Different materials were also added to the culture medium with the high dose of glucose for another 24 hours to investigate their ability to regulate glucose metabolism or NF‐κB2. Ganoderic acid A (Cat#81907622, Derick, Chengdu, China, treated concentration: 0.25 μM) was used for its function of antioxidative activities, intracellular reactive oxygen species (ROS) scavenging, inhibitory effect on NF‐κB, and inhibition of the glucose metabolic shift 33‐36 . Galloflavin (Cat#568‐80‐9, Aladdin, Los Angeles, USA, treated concentration: 100 μM) was used for the inhibition of overactivated fermentative glycolysis 37 .…”
Section: Methodsmentioning
confidence: 99%
“…lucidum that support its antioxidant and protective effects. A pancreatic cell study suggested β -catenin in the Wnt signaling pathway as a target of ganoderic acid A, thus leading to cell protection and effective scavenging of ROS [ 54 ]. The Wnt signaling pathways transfer the signals from extracellular to intercellular and are stimulated by the Wnt protein binding to the cytoplasmic family receptor, which occurs in downstream cell signaling and controls the transcription of genes.…”
Section: Resultsmentioning
confidence: 99%
“…mTOR is the main target of G. lucidum, and this finding supports its antioxidant and cardioprotective effects. G. lucidum inhibits the Wnt pathway [54] and may decrease the activity of mTOR via the Wnt/GSk/mTOR signal pathway. A pathologically stressed heart reactivates the Wnt signal pathway, which is modulated during left ventricular remodeling [77].…”
mentioning
confidence: 99%
“…Data from Wang et al have reported that GA‐A impairs proliferation and invasion, and promotes apoptosis in human hepatocellular carcinoma cells. Gill et al have suggested that GA‐A inhibits properties of proliferation and viability, and intracellular ROS of pancreatic cancer cells. Significantly, GA‐A heightens chemosensitivity of hepatocellular carcinoma cells to Cisplatin, raising its possibility for being utilized as a perspective combined chemotherapeutic agents for cancer treatment .…”
Section: Discussionmentioning
confidence: 99%